2013
DOI: 10.1016/j.pscychresns.2013.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

Neural processing correlates of assaultive violence exposure and PTSD symptoms during implicit threat processing: A network-level analysis among adolescent girls

Abstract: Assaultive violence exposure during childhood is a significant risk factor for posttraumatic stress disorder (PTSD). The purpose of the present study was to characterize the relationships of assault and PTSD severity with the organization of large-scale networks identified during emotion processing. Adolescent girls aged 12–16 with (N=15) and without (N=15) histories of assault underwent fMRI while engaged in a task that presented images of fearful or neutral facial expressions. Independent component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 79 publications
9
90
1
Order By: Relevance
“…Although dACC hyperactivation has been a relatively consistent finding in adult PTSD (Pitman et al, 2012), it has not previously been reported in pediatric PTSD/PTSS. This may be attributable to differences in emotion task, but could also be related to greater PTSD severity in our sample as compared with prior studies (eg, Cisler et al, 2013;Crozier et al, 2014;Garrett et al, 2012). Interestingly, we did not find evidence of abnormal amygdala-dACC connectivity in pediatric PTSD.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although dACC hyperactivation has been a relatively consistent finding in adult PTSD (Pitman et al, 2012), it has not previously been reported in pediatric PTSD/PTSS. This may be attributable to differences in emotion task, but could also be related to greater PTSD severity in our sample as compared with prior studies (eg, Cisler et al, 2013;Crozier et al, 2014;Garrett et al, 2012). Interestingly, we did not find evidence of abnormal amygdala-dACC connectivity in pediatric PTSD.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, only one reported study has examined functional brain connectivity in youth with PTSS. A study of adolescent sexual assault victims, largely subclinical for PTSD, reported an inverse relationship between PTSS and amygdala-rACC functional connectivity, although no group differences in connectivity were reported (Cisler et al, 2013). These studies provide initial evidence of abnormal prefrontal-amygdala function during emotion processing in pediatric PTSD, yet their differing findings also highlight the need for additional study.…”
Section: Introductionmentioning
confidence: 82%
“…One possible reason for this is greater PTSD severity and comorbidity within the current sample, where other studies have recruited youth based on lower symptom thresholds. Finally, Cisler et al (2013) found a negative relationship between PTSD symptom severity and amygdala-dmPFC/pre-SMA connectivity to fearful faces in girls with a history of assault. This is perhaps one of the most consistent findings to date in pediatric PTSD/PTSS, with both the current study and our prior study (Wolf and Herringa, 2016) showing decreased amygdala-dmPFC connectivity to negative emotional stimuli, and further predicting PTSD severity.…”
Section: Discussionmentioning
confidence: 83%
“…Decreased dmPFC activation to fear faces has been reported in female youth with PTSS, suggesting possible sex differences (Crozier et al, 2014). Finally, PTSS were found to be negatively correlated with amygdala-dmPFC/pre-supplementary motor area (SMA) functional connectivity to fear versus neutral faces (Cisler et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…61 Interestingly, one study reported inappropriate activation of the DMN during a working memory task among patients with PTSD that contrasted with appropriate activation of the CEN among controls, suggesting an inability to recruit task-positive networks in individuals with PTSD. 99 In addition, reduced resting state functional connectivity among frontoparietal regions of the CEN have been associated with PTSD symptoms and trauma history 100 ( Fig. 2).…”
Section: The Triple Network Model Of Psychopathology and Ptsdmentioning
confidence: 99%